The Effect of Audit Committee, Independent Commissioners, Leverage, Audit Quality, and Audit Tenure on the Integrity of Financial Reports (Empirical Study on Mining Companies in the Oil, Gas & Coal Sub-Sector Listed on the Indonesia Stock Exchange for the - Sulaeman Al Rasid; Yudhi Herliansyah; Suharmadi Suharmadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study empirically tests the influence of the Audit Committee, Independent Commissioners, Leverage, Audit Quality, and Audit Tenure on the Integrity of Financial Statements in Mining Companies in the Oil, Gas & Coal Sub-Sector listed on the Indonesia Stock Exchange during 2019 - 2022. The object of this study use Mining Companies in the Oil, Gas & Coal Sub-Sector listed on the Indonesia Stock Exchange during 2019 - 2022. The sample of this study is 92 samples from 23 companies that meet the sampling criteria. The purposive sampling method was used in this study. The method used in this study is multiple linear analysis consisting of Independent variables and Dependent variables using SPSS 25 software. The results of this study indicate that the Audit Committee does not affect the Integrity of Financial Statements, Independent Commissioners have an effect on the Integrity of Financial Statements, Leverage has no impact on the Integrity of Financial Statements, Audit Quality has no effect on the Integrity of Financial Statements, Audit Tenure has no effect on the Integrity of Financial Statements.